INDONESIAN TRADITIONAL GAME «BANDHUL SADA» IN LEARNING ROTATION DYNAMIC CONCEPTS WITH CONTEXTUAL APPROACH - Siska Desy Fatmaryanti (Фізико-математична освіта)
Teachers can support cultural preservation while also providing a relevant and interesting way to teaching diverse subjects by including traditional games into the learning process. The aim of this research is identify the rotation dynamic concepts of Indonesian traditional game «Bandhul Sada» with contextual approach